PENERAPAN PBL BERBASIS STEM BERBANTU MEDIA BUNGA PECAHAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS III DI SD 2 DEMAAN - Vira Ayu Ningrum; F. Shoufika Hilyana; Lovika Ardana Riswari (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
This exploration was roused by the low decisive reasoning abilities of class III understudies at SD 2 Demaan in partaking in topical learning, particularly in Arithmetic subject substance. The purpose of this study is to find out how fractional interest media and the STEM-based PBL learning model affect the critical thinking skills of class III students at SD 2 Demaan. This examination utilizes a quantitative exploratory plan with a one gathering pretest-posttest plan. The information assortment procedure utilizes a composed test with FRISCO decisive reasoning pointers which are depicted as F (Concentration), R (Reason), I (Derivation), S (Circumstance), C (Lucidity), and O (Outline). The examination area is in class III of SD 2 Demaan. The example in this study comprised of 18 understudies utilizing soaked testing methods. As well as involving information examination as approval tests, information ordinariness tests, basic straight relapse tests. The consequences of this examination show that the straightforward direct relapse test got a tcount worth of 7.854 > ttable 2.120, so the use of the STEM-based Issue Based Getting the hang of learning model helped by partial interest media (X) impacts understudies' decisive reasoning skills (Y). In light of the exploration results, it very well may be presumed that there is an impact of the STEM-based PBL learning model helped by partial interest media on understudies' decisive reasoning skills at SD 2 Demaan. Kata Kunci: PBL, STEM, Bunga Pecahan, Berpikir Kritis